Skarb z epoki brązu z Bolesławca, pow. wieruszowski - Marchelak, Ireneusz; Ziąbka, Leszek (Folia Praehistorica Posnaniensia, 2016)
The paper presents a hoard of bronze objects from Bolesławiec, Wieruszów District, deposited within the Upper Silesian-Małopolska zone of the Lusatian urnfields. The hoard comprises ornaments and devices used to fasten clothing that are indicative of both an interregional context and local production centres. The hoard dates to Phase IV/Phase V of the Bronze Age, or perhaps a somewhat later period, and fits with the picture of complex and intense cultural processes taking place in the Upper Silesian-Małopolska zone at the time.